UANG DAN HAL - HAL LAIN DALAM PEMILIHAN KEPALA DESA (PILKADES) TAHUN 2017 - Femila Rizky Damayanti; Wijayanto - -; Puji - Astuti (Journal of Politic and Government Studies, 2022)
The election of the village headman is a representation of electoral democracy that is closely related to the real life of the community. Voters are relatively more acquainted with and know the candidates who competed in this election compared to candidates at other higher level elections because they live in the same environment. This condition makes voter behavior at the village headman election interesting to study. This research aims to examine voter behavior and the phenomenon of money politics at the Bungo Village Headman Election in Demak Regency in 2017. Through a series of interviews and documentation, the researcher tries to present an analysis of the factors that influence the Bungo Village community in determining their choice in the Bungo Village Headman Election, Demak Regency 2017. This research confirms that there are several factors that influence the community in choosing candidates for village heads such as, these factors include; money politics factors, sociological factors, psychological factors, and rational choice factors